Attitudes of Suicide Prevention Workers toward Euthanasia - Kaur, Jaskiran (Université d'Ottawa / University of Ottawa, 2018)
Extensive research has been conducted on the attitudes of physicians and nurses toward euthanasia. However, little is known on the attitudes of suicide prevention workers (SPWs). The objectives of this study were to: (1) examine the attitudes of SPWs toward euthanasia for a non-descript person versus for a loved one; (2) verify the association between personal factors (experiences, sociodemographics) and attitudes, and (3) explore personal experiences of SPWs in relation to grievous illness. A survey was sent out to all suicide prevention centres across Quebec (n=32). A majority of SPWs (55.7%) held positive attitudes toward euthanasia for a non-descript person and for a loved one (49.5%). Statistically significant differences were found in attitudes among SPWs who had personal and professional experiences. There were no other statistically significant differences in the attitudes of SPWs toward euthanasia for a non-descript person or for a loved one, and any of the sociodemographic factors. Three themes emerged from the qualitative analysis of open-ended question on personal experiences of SPWs: respect of choice, suffering/low quality of life and palliative care. While some findings may be concluded from this study, it is essential that this topic be explored further as research on SPWs’ attitudes on euthanasia is limited. Research outcomes of this study can have important short-term and long-term implications on suicide prevention and training of SPWs to improve services offered to clients.
Keywords: Euthanasia; Physician-assisted suicide; Suicide; Attitudes; Quebec; Mental Health Workers